Applications of omega-3 polyunsaturated fatty acid supplementation for sport performance. Issue 2 (3rd April 2019) - Philpott, Jordan D.; Witard, Oliver C.; Galloway, Stuart D.R.
ABSTRACT: Omega-3 (n-3) polyunsaturated fatty acid (PUFA) supplementation has recently been proposed as an ergogenic aid for athletes. This claim is primarily based on mechanistic evidence that n-3PUFA's exert anti-inflammatory properties and act to change the functional capacity of the muscle cell by modifying the membrane fluidity of proteins and lipids within the cell membrane. In this review, we critically evaluate the scientific literature that examines the efficacy of n-3PUFA supplementation to improve athlete performance within the context of promoting muscle adaptation, energy metabolism, muscle recovery and injury prevention (e.g. muscle loss during immobilisation, or concussion). These findings have applications to athletes competing in strength/power-, endurance- and team-, based sports. Based on available information, there is some scientific evidence that n-3PUFA supplementation may improve endurance capacity by reducing the oxygen cost of exercise. Moreover, several studies report a benefit of n-3PUFA supplementation in promoting recovery from eccentric-based muscle damaging exercise. In contrast, there is insufficient evidence from studies in athletic populations to support the claim that n-3PUFA supplementation facilitates muscle growth during resistance training or preserves muscle mass during catabolic scenarios such as energy restriction or immobilisation. Moving forward, there remains ample scope to investigate context-specific applications of n-3PUFA supplementation for sport performance.